2016
DOI: 10.1039/c5nj03152d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the N-based ligands in copper complexes for depolymerisation of lignin

Abstract: Several organic soluble N-based ligands and their copper complexes were firstly investigated as catalysts to depolymerise organosolv lignin in the organic solvent, dimethylformamide (DMF) and an ionic liquid (1-ethyl-3-methylimidazolium xylenesulfonate, [emim][ABS]). The results of screening depolymerisation reactions in DMF and [emim] [ABS] showed that all the copper-amine complexes catalysed lignin depolymerisation more efficiently in ionic liquids than in DMF. Among the seven types of ligands, copper compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Ligands (L n = L‐a–L‐c) in the current study were synthesized as reported previously . Complexes, [(L) n MX 2 ] m (L = L‐a–L‐c; M = Zn, Pd; X = Cl; M = Cd; X = Br; n , m = 1 or 2; 67–98% yields), were obtained by direct ligation of metal starting materials with ligands in 1:1 ratio in CH 3 CN or EtOH at ambient temperature (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ligands (L n = L‐a–L‐c) in the current study were synthesized as reported previously . Complexes, [(L) n MX 2 ] m (L = L‐a–L‐c; M = Zn, Pd; X = Cl; M = Cd; X = Br; n , m = 1 or 2; 67–98% yields), were obtained by direct ligation of metal starting materials with ligands in 1:1 ratio in CH 3 CN or EtOH at ambient temperature (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Modified methylaluminoxane (MMAO) was purchased from Tosoh Fine Chemicals as 5.90% weight aluminum of a toluene solution and used without further purification. Ligands L‐a , L‐b and L‐c have been prepared by literature methods. Complexes [(L‐a)PdCl 2 ] , [(L‐a)ZnCl 2 ] , ( [(L‐a)Cd(μ – Br)Br] 2 and [(L‐b)PdCl 2 ] have been synthesized as described previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common lignins, such as organosolv lignin, alkali soluble lignin and kraft lignin were selected for screening the depolymerization reaction. A methanol separation method was presented in our previous work …”
Section: Resultsmentioning
confidence: 99%
“…7,18 Compared to other methods, lignin reduction and oxidation methods utilize milder conditions to degrade lignin, which can thus be suitable for the industry. 19,20 Our group has previously reported several oxidative lignin depolymerization strategies 21,22 and also reviewed the recent developments in the chemical degradation of lignin involving catalytic oxidation. 23 Lignin catalytic oxidation methods normally show high selectivity in the products formed.…”
Section: Introductionmentioning
confidence: 99%